Calculation the pressure in a zone of contact of rigid sphere with the viscoelastic environment - Кузяев, И.М.; Буря, А.И. (Problems of Tribology, 2014)
Results of the decision of a contact problem of interaction of a rigid stamp with a spherical surface with a viscoelastic surface are presented.